1984
DOI: 10.1139/v84-179
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of hydrocarbons. 12. Kinetics and mechanism of the oxidation of trans-cinnamic acid by ruthenate and perruthenate ions

Abstract: , 1085 (1984). Recent theoretical calculations by RappC and Goddard have pointed to the importance of spectator 0x0 groups in stabilizing intermediates produced during thc reduction of high-valent transition metal oxides; intermediates which contain triply-bonded metal 0x0 groups are predicted to be unusually stable. In an attempt to test these conclusions experimentally, the rates of oxidation of cinnamate ion by ruthenate and permthenate ions have been studied. Since the most likely intermediate formed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The differentiation between route A and B in scheme 20 can be rationalized from the introduction of the spectator oxo bond. 69,70,147 The preference of either C or D can to some degree be traced to the bond energies of the resulting oxometal or carbenemetal species, respectively. 73,74 In the case of titanium route C will be favored, as the bond energy of Ti=0 is larger than the Ti=CH2 bond energy; this is probably the driving force in the "Tebbe-like" reactions.…”
Section: R1mentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiation between route A and B in scheme 20 can be rationalized from the introduction of the spectator oxo bond. 69,70,147 The preference of either C or D can to some degree be traced to the bond energies of the resulting oxometal or carbenemetal species, respectively. 73,74 In the case of titanium route C will be favored, as the bond energy of Ti=0 is larger than the Ti=CH2 bond energy; this is probably the driving force in the "Tebbe-like" reactions.…”
Section: R1mentioning
confidence: 99%
“…141 It was proposed that the alkene-permanganate complex 74 was first formed, followed by a rate-determining nucleophilic attack by one of the oxygen atoms in the permanganate ion at the carbon atom nearest the aromatic ring initiated by a slipping motion of the alkene along the C=C bond, producing the metallaoxetane 75 (Scheme 14). The metallaoxetane then rearranges to the cyclic manganese(V) ester 76.141 The idea with the slipping motion of the alkene toward one of the oxygens and subsequent formation of the metallaoxetane has been used by Lee The spectator oxo bond introduced by Rappe and Goddard to be able to stabilize intermediates persuaded Lee et al 147 to investigate the oxidation of trans-cinnamic acid by ruthenate (Ru042~) and perruthenate (Ru04"). The purpose of using ruthenate and perruthenate was the following: it was assumed that the metaUaoxetane intermediates were formed in rapid equilibrium reactions and that the perruthenate ion would react more rapidly with the carbon-carbon double bond to give the cyclic ruthenium(V) diester 77 (reaction 17) because 77 is stabilized by the spectator oxo group.147 However, the similar reaction with ruthenate would not occur so readily (reaction 18), because of the formation of the cyclic ruthenium(IV) diester intermediate 78 could only be achieved by loss of the stability associated with the presence of the spectator oxo group in the metaUaoxetane 79.147 It was concluded that the experimental observation was in agreement with the predictions made by Rappe and Goddard.69 In a study of the mechanism of cyclization of tripeptides by the enzyme isopeniciUn N synthase (IPNS) a ferraoxetane 81 formed by a [27t + 2ir] cycloaddition of the oxo-iron species to the double bond has been postulated (reaction It was found that the reaction rate for the oxidation of cinnematic ion with perruthenate ion was 5 x 10® times faster than the corresponding ruthenate reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…-k -, [1] Because the values of the observed rate constant depend directly on the magnitude of k l (which would, in turn, be reduced by deuterium substitution at the a-hydrogen) a primary isotope effect results. The negative entropy of activation, AS* = -23 2 1 eu, observed for the oxidation of 2-propanol by ruthenate, indicates that the rate-limiting step, in common with most second order reactions, involves an increase in organization of the transition state as compared to the ground state.…”
Section: Imentioning
confidence: 99%